Understanding the Hydrogen Evolution Reaction Kinetics of Electrodeposited Nickel‐Molybdenum in Acidic, Near‐Neutral, and Alkaline Conditions. Issue 1 (5th January 2021) - Bao, Fuxi; Kemppainen, Erno; Dorbandt, Iris; Bors, Radu; Xi, Fanxing; Schlatmann, Rutger; van de Krol, Roel; Calnan, Sonya
Abstract: Nickel‐molybdenum (NiMo) alloys can be a possible alternative to platinum as hydrogen evolution reaction (HER) catalysts because of the superior HER activity. However, the superior HER activity and the pH‐dependent kinetics are not currently fully understood. Herein, we present a study of HER kinetics and mechanisms of NiMo in alkaline, near‐neutral and acidic media by combining voltammetry measurements with electrochemical impedance spectroscopy and a microkinetic model. The results indicate that, compared to Ni, NiMo has significantly higher active surface area and intrinsic HER activity. In the subsequent measurements, we demonstrated that different from the existing explanations to the HER mechanisms for NiMo, the HER process in acidic, near‐neutral, and alkaline media is controlled by the Heyrovsky step. Our results show that increasing pH increases the hydrogen coverage, which increases the Tafel‐slope at low overpotentials, eventually resulting in only a single Tafel slope, which would commonly be interpreted as a Volmer‐limited reaction. Furthermore, the studies of thickness effect on HER kinetics show that the HER kinetics of NiMo are thickness‐dependent. In phosphate buffer, the increase in thickness did not significantly increase the double‐layer capacitance, but simulations with the microkinetic model indicate that the active surface area still increased similarly to other electrolytes, which is likely related to the type of electrolyte used. Abstract : HER mechanisms on NiMo : The hydrogen evolution reaction (HER) in acidic, near‐neutral, and alkaline conditions proceeds via the Volmer‐Heyrovsky path with Heyrovsky as the rate‐determining step. Increasing pH makes the Volmer step faster relative to Heyrovsky, which leads to the increase in hydrogen coverage on NiMo surface and eventually to a single Tafel‐slope (>120 mV dec ‐1 ).